2000
DOI: 10.1161/01.res.86.9.960
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Peroxide– and Peroxynitrite-Induced Mitochondrial DNA Damage and Dysfunction in Vascular Endothelial and Smooth Muscle Cells

Abstract: The mechanisms by which reactive species (RS) participate in the development of atherosclerosis remain incompletely understood. The present study was designed to test the hypothesis that RS produced in the vascular environment cause mitochondrial damage and dysfunction in vitro and, thus, may contribute to the initiating events of atherogenesis. DNA damage was assessed in vascular cells exposed to superoxide, hydrogen peroxide, nitric oxide, and peroxynitrite. In both vascular endothelial and smooth muscle cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
262
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 389 publications
(282 citation statements)
references
References 45 publications
19
262
1
Order By: Relevance
“…For instance, H 2 O 2 treatment has been shown to promote extensive mtDNA damage through generation of apurinic sites, strand breaks and base modifications. 19,20 To investigate whether mtDNA chemical damage would also activate Akt2 signaling thus mirroring the effects of mtDNA depletion, we treated wild-type PNT1A cells with either 2.5 or 5 mM H 2 O 2 for up to 1 h, after which H 2 O 2 -containing medium was replaced with fresh medium. Higher H 2 O 2 concentrations proved to be cytotoxic (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, H 2 O 2 treatment has been shown to promote extensive mtDNA damage through generation of apurinic sites, strand breaks and base modifications. 19,20 To investigate whether mtDNA chemical damage would also activate Akt2 signaling thus mirroring the effects of mtDNA depletion, we treated wild-type PNT1A cells with either 2.5 or 5 mM H 2 O 2 for up to 1 h, after which H 2 O 2 -containing medium was replaced with fresh medium. Higher H 2 O 2 concentrations proved to be cytotoxic (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…As opposed to nuclear-encoded genes, mitochondrial-encoded gene expression is largely regulated by the copy number of mtDNA (12). Therefore, mitochondrial injury is reflected by mtDNAdamage as well as by a decline in the mitochondrial RNA(mtRNA) transcripts, protein synthesis, and mitochondrial function (13,14). Wehave recently shown that the increased generation of ROSwas associated with mitochondrial damage and a dysfunction in the failing hearts, which were characterized by an increased lipid peroxidation in the mitochondria, a decreased mtDNAcopy number, a decrease in the numberof mtRNA transcripts, and a reduced oxidative capacity due to low complex enzyme activities (15).…”
Section: Oxidant Stress In Failing Heartsmentioning
confidence: 99%
“…NO induces cell death through mechanisms involving cytochrome c release and caspase activation (7,8). Furthermore, ROS can induce mitochondrial DNA damage in endothelial cells, and this damage is accompanied by a decrease in mitochondrial RNA (mtRNA) transcripts, mitochondrial protein synthesis, and cellular ATP levels (9). Mitochondria have been recognized to play a pivotal role in the signaling cascade of apoptosis (10) and have been implicated in atherosclerosis-induced damage in endothelial cells (11,12).…”
mentioning
confidence: 99%